Controllable Synthesis of Carbon Yolk‐Shell Microsphere and Application of Metal Compound–Carbon Yolk‐Shell as Effective Anode Material for Alkali‐Ion Batteries. Issue 3 (18th January 2023) - Kim, Yeong Beom; Seo, Hyo Yeong; Kim, Sang‐Hyun; Kim, Tae Ha; Choi, Jae Hyeon; Cho, Jung Sang; Kang, Yun Chan; Park, Gi Dae
Abstract: Recently, nanostructured carbon materials, such as hollow‐, yolk‐, and core‐shell‐configuration, have attracted attention in various fields owing to their unique physical and chemical properties. Among them, yolk‐shell structured carbon is considered as a noteworthy material for energy storage due to its fast electron transfer, structural robustness, and plentiful active reaction sites. However, the difficulty of the synthesis for controllable carbon yolk‐shell has been raised as a limitation. In this study, novel synthesis strategy of nanostructured carbon yolk‐shell microspheres that enable to control morphology and size of the yolk part is proposed for the first time. To apply in the appropriate field, cobalt compounds‐carbon yolk‐shell composites are applied as the anode of alkali‐ion batteries and exhibit superior electrochemical performances to those of core‐shell structures owing to their unique structural merits. Co3 O4 ‐C hollow yolk‐shell as a lithium‐ion battery anode exhibits a long cycling lifetime (619 mA h g −1 for 400 cycles at 2 A g −1 ) and excellent rate capability (286 mA h g −1 at 10 A g −1 ). The discharge capacities of CoSe2 ‐C hollow yolk‐shell as sodium‐ and potassium‐ion battery anodes at the 200th cycle are 311 mA h g −1 at 0.5 A g −1 and 268 mA h g −1 at 0.2 A g −1, respectively. Abstract : A novel synthetic strategy for nanostructured carbon yolk‐shell microspheres that enables to control morphology and size of the carbon yolk in the microsphere is introduced. To the best of our knowledge, from hollow yolk‐shell to dense core‐shell structure with almost no empty space as a yolk gradually forms, a method to easily control the carbon nanostructure is proposed for the first time. The yolk‐shell structured cobalt oxide‐C, cobalt selenide‐C showed good cycle performances and excellent rate capabilities for alkali‐ion batteries.